IgE antibodies increase honeybee venom responsiveness and detoxification efficiency of mast cells. Issue 2 (6th May 2021) - Starkl, Philipp; Gaudenzio, Nicolas; Marichal, Thomas; Reber, Laurent L.; Sibilano, Riccardo; Watzenboeck, Martin L.; Fontaine, Frédéric; Mueller, André C.; Tsai, Mindy; Knapp, Sylvia; Galli, Stephen J.
Abstract: Background: In contrast to their clearly defined roles in allergic diseases, the physiologic functions of Immunoglobulin E antibodies (IgEs) and mast cells (MCs) remain enigmatic. Recent research supports the toxin hypothesis, showing that MCs and IgE‐related type 2 immune responses can enhance host defense against certain noxious substances, including honeybee venom (BV). However, the mechanisms by which MCs can interfere with BV toxicity are unknown. In this study, we assessed the role of IgE and certain MC products in MC‐mediated BV detoxification. Methods: We applied in vitro and in vivo fluorescence microscopyimaging, and flow cytometry, fibroblast‐based toxicity assays and mass spectrometry to investigate IgE‐mediated detoxification of BV cytotoxicity by mouse and human MCs in vitro . Pharmacologic strategies to interfere with MC‐derived heparin and proteases helped to define the importance of specific detoxification mechanisms. Results: Venom‐specific IgE increased the degranulation and cytokine responses of MCs to BV in vitro . Passive serum sensitization enhanced MC degranulation in vivo . IgE‐activated mouse or human MCs exhibited enhanced potential for detoxifying BV by both proteolytic degradation and heparin‐related interference with toxicity. Mediators released by IgE‐activated human MCs efficiently degraded multiple BV toxins. Conclusions: Our results both reveal that IgE sensitization enhances the MC's ability to detoxify BV and also assign efficient toxin‐neutralizing activity to MC‐derived heparin and proteases. Our study thus highlights the potential importance of IgE, MCs, and particular MC products in defense against BV. Abstract : Immunoglobulin E antibodies increase mast cell responsiveness to honeybee venom in vitro and in vivo . Compounds released by IgE‐activated mouse and human mast cells can efficiently detoxify honeybee venom. Mast cell‐derived heparin and proteases contribute to prevention of honeybee venom toxicity